Impact of diagnosis and therapy on cognitive function in urea cycle disorders - Posset, Roland; Baumgartner, Matthias R.; Zielonka, Matthias; Hoffmann, Georg F.; Burgard, Peter; Kölker, Stefan (Annals of neurology, 2019)
Objective:Individuals with urea cycle disorders (UCDs) often presentwith intellectual and developmental disabilities. Themajor aim of this study was to evaluate the impact of diagnostic and therapeutic interventions on cognitive outcomes in UCDs.Methods:This prospective, observational, multicenter study includes data from 503 individuals with UCDs who hadcomprehensive neurocognitive testing with a cumulative follow-up of 702 patient-years.Results:Themeancognitivestandarddeviationscore(cSDS) was lower in symptomatic than in asymptomatic (p< 0.001,ttest)individuals with UCDs. Intellectual disability (intellectual quotient < 70, cSDS <−2.0) was associated with the respective subtype ofUCD and early disease onset, whereas height of the initial peak plasma ammonium concentration was inversely associated withneurocognitive outcomesin mitochondrial (proximal) rather than cytosolic (distal) UCDs. In ornithine transcarbamylase andargininosuccinate synthetase 1 deficiencies, we did notfind evidence that monoscavenger therapy with sodium or glycerolphenylbutyrate was superior to sodium benzoate in providing cognitive protection. Early liver transplantation appears to be bene-ficial for UCDs. It is noteworthy that individuals with argininosuccinate synthetase 1 and argininosuccinate lyase deficiencies identi-fied by newborn screening had better neurocognitive outcomes than those diagnosed after the manifestation offirst symptoms.Interpretation:Cognitive function is related to interventional and non-interventional variables. Early detection by new-born screening and early liver transplantation appear to offer greater cognitive protection, but none of the currentlyused nitrogen scavengers was superior with regard to long-term neurocognitive outcome. Further confirmation coulddetermine these variables as important clinical indicators of neuroprotection for individuals with UCDs.